Nitrate Increases Cadmium Accumulation in Sweet Sorghum for Improving Phytoextraction Efficiency Rather Than Ammonium - Bai, Zhenqing; Li, Dan; Zhu, Lin; Tang, Xiaoyu; Wang, Yanfeng; Mao, Renjun; Wu, Jiawen (Frontiers in Plant Science, 2021)
Sweet sorghum has potential for phytoextraction of cadmium (Cd) owning to its large biomass and relatively high Cd tolerance. Nitrogen affects both growth and Cd concentrations in plants. However, different forms of nitrogen effects on Cd accumulation in sweet sorghum to improve efficiency of Cd phytoremediation is still elusive. In this study, nitrate substantially promoted both dry weight and Cd concentrations in leaves, stems+sheaths and roots of sweet sorghum when compared with ammonium. As a result, Cd accumulation in nitrate-supplied sweet sorghum was around 3.7-fold of that in ammonium-supplied plants under unbuffered pH condition, while the fold was about 2.2 under buffered pH condition. We speculated pH values and Cd species in the growth medium to some extent contributed to increased Cd accumulation as affected by nitrate. Net photosynthesis rate and Fv/Fm of nitrate-treated plants under Cd stress were higher than that of ammonium-treated plants when the pH was unbuffered. Responses of antioxidant capacity in roots to Cd stress with nitrate application were stronger than that with ammonium supplementation. Taken together, nitrate is more suitable than ammonium for Cd phytoextraction by using sweet sorghum, which is able to enhance at least double efficiency of phytoextraction.